Gambaran Sense of Humor pada Mahasiswa yang Terdiagnosis Anxiety - Panggih Alfarisy; Mustaqim Setiyo Ariyanto; Andhita Dyorita Khoiryasdien (EduInovasi: Journal of Basic Educational Studies, 2025)
Humor has probably existed since humans knew language, or even older. If we trace its origins, humor comes from the Latin word umor which means 'fluid'. Since 400 BC, the ancient Greeks thought that human mood was determined by four types of fluids in the body, namely blood (sanguis), mucus (phlegm), yellow bile (choler), and black bile (melancholy). There are many humor theories, none of which are exactly the same as each other, none of which can describe humor completely, and all tend to be influenced by each other. For students, humor itself functions as a way to lighten the atmosphere when gathering. This research uses qualitative research methods where the research subjects are students who are diagnosed with symptoms of anxiety. The results of this research are that the subject really likes to make people around him laugh, but if when he tells a joke and no one responds the subject will feel panicked, anxious, uncomfortable, uncomfortable and embarrassed, which will then become pressure for the subject. Based on the research results, there were no significant changes in humor in the subjects. In this case, the subject is not only diagnosed with anxiety, but there are also other diagnoses such as depression.